Credit’s use performance and its determinants on farm household: A case of Chitwan district of Nepal - Upadhyay, Namdev; Gairhe, Samaya; Acharya, Yogendra; Ghimire, Yuga Nath; Timsina, Krishna Prasad; Acharya, Ashok (Journal of Agriculture and Natural Resources, 2020)
Credit has been considered to play a pivotal role in the agricultural development of Nepal. A large number of institutions are involved in the disbursement of credit to agriculture. In this backdrop, the present study has examined the performance of agricultural credit and has identified the determinants of increased use of credit at the farm household level in Nepal. The study was based on survey data consisting of 107 samples collected randomly from the Chitwan district. The study has revealed that the quantum of credit availed by the farming households is affected by several socio-demographic factors which include caste, economically active population, food sufficiency, and membership in an organization. The research revealed that if the household is Brahmin/ Chettri, the probability of borrowing loans decreased by 32% as compared to other castes. Similarly, if the household’s economically active population increased by one unit, the probability of taking a loan increased by 16%. The results also show that, if household food sufficiency increased by one month the probability of taking loans decreased by 4 % but if the household head is a member of an organization, the probability of taking a loan increased by 28%. The congenial environment to increase the involvement of the household head to an organization like cooperative and farmers group, increasing the food self-sufficiency through productivity enhancement program and creating awareness on credit utilization helps to increase credit use performance in Agriculture.